Effect of water stress on tomato landraces mexican - Maldonado-Peralta, Ramiro; Maldonado-Peralta, María de los Ángeles; Rojas-García, Adelaido Rafael; Salinas Vargas, Delfina (Ecosistemas y Recursos Agropecuarios, 2021)
ABSTRACThere is a need to use water effectively and efficiently, because water availability is scarce and it is the main limiting factor in agricultural production. This study was conducted to compare the water stress response (25%) of four native tomato populations and one commercial hybrid, compared to a sufficient irrigation regime (100%). The variables evaluated during the growing cycle were: chlorophyll, leaf area, yield, weight per fruit, number of fruit, number of locules, firmness, total soluble solids and biomass. The results show that all the agronomic and fruit quality characteristics presented significant differences (P ≤ 0.05). The commercial variety Cid F1 (Harris Moran®) in irrigation (100%) presented twice the foliar area than the Campeche population. The water deficit caused a decrease in leaf area in all genotypes and the control was the most affected (35%). The highest yield in four bunches was produced by the control and Oaxaca 100% (3.7 and 3.6 kg plant-1) and the lowest production was the Campeche 100% population (2.2 kg plant-1). The water deficit caused a reduction in yield, in the Oaxaca variety (64%),turning out to be the most affected. In conclusion, the genotypes with the highest  yield were more affected by the hybrid deficit, which increased soluble solids, in those genotypes with the lowest yield.